Factors influencing flood disaster preparedness initiatives among small and medium enterprises located at flood-prone area - Hashim, Hajar Mariah; Ng, Yee Guan; Talib, Othman; Md Tamrin, Shamsul Bahri (Elsevier, 2021)
This paper highlights the factors affecting SMEs flood disaster preparedness located in Segamat District of Malaysia. An interviewer-assisted survey using a set of flood disaster preparedness questionnaire (developed and validated by a team of disaster management experts from various background) were implemented among Small and Medium Enterprises (SMEs) business owners and managers (n = 253). The analysis of regression provided insights into the various factors affecting the contribution of small and medium-sized businesses towards flood preparedness activities. Findings demonstrated that risk perception is the most consistent factors in influencing preparedness actions. Besides that, previous experiences on floods, retails sectors and male ownership also contributed to a high level of flood disaster preparedness engagement. This research gave insight at why small and medium-sized businesses are involved in disaster preparedness activities which includes discussion from a review of previous findings.